Stereotactic body radiotherapy for operable, early stage non-small cell lung cancer—let’s all take a deep breath - Howell, Eric B.; Berfield, Kathleen S.; Wood, Douglas E. (Journal of Thoracic Disease; Vol 10, Supplement 17 (June 20, 2018): Journal of Thoracic Disease, 2018)
In spite of a federally mandated emphasis on smoking cessation and primary prevention, lung cancer remains by far the most common cause of cancer death and carries a 5-year survival rate (~18%) that is far lower than that of other leading cancers (1).